Célébrer Cesare Lombroso (1906-1909) - Silvano Montaldo (Revue d’Histoire des Sciences Humaines)
This article reconstructs the commemorations organised in 1906 for the thirty years of Cesare Lombroso's teachings in Turin, and for his funeral three years later. By analysing the debate which took place in the City Council, and Lombroso's correspondence with the authorities, a singular figure emerges (as a Jew, a materialist and a socialist), despite the formality of the commemorations. The letters written to him by his admirers and disciples reveal the impact of Lombroso's ideas on the scientific and political figures of Southern Italy, and reframe the polemic on Lombroso's supposed anti-Southern racism. The reconstruction of the arrangements after Lombroso's death, in 1909, confirms how different he was from the ruling class of his day. His choice of a secular ceremony, close to a minority tradition, yet firmly anchored in positivism, again demonstrates Lombroso's non-conformist character.